2011
DOI: 10.1186/1756-0500-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Caries-preventive effect of glass ionomer and resin-based fissure sealants on permanent teeth: An update of systematic review evidence

Abstract: BackgroundThis article constitutes a partial update of the original systematic review evidence by Yengopal et al. from 15 January 2008 (published in the Journal of Oral Science in 2009) with primary focus on research quality in regard to bias risk in trials. Its aim is to update the existing systematic review evidence from the English literature as to whether caries occurrence on pits and fissures of teeth sealed with either GIC or resin is the same.MethodsIn addition to the 12 trials included during the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 44 publications
6
57
0
3
Order By: Relevance
“…However, a clinical study showed that glass ionomer sealants were slightly more efficient in preventing caries than resin-based 32) . The outcomes of our clinical trial are in agreement with the conclusions of earlier published systematic reviews and meta-analyses comparing resin-based and glass-ionomer sealants 19,20) . In terms of retention, both sealants performed better in the 6-7-year age group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, a clinical study showed that glass ionomer sealants were slightly more efficient in preventing caries than resin-based 32) . The outcomes of our clinical trial are in agreement with the conclusions of earlier published systematic reviews and meta-analyses comparing resin-based and glass-ionomer sealants 19,20) . In terms of retention, both sealants performed better in the 6-7-year age group.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, glass ionomer cement has the advantage of being moisture tolerant and offering continuous fluoride release; however, its effect on caries prevention is questionable because of its inadequate retention rate 15,16) . Although numerous clinical studies have provided conflicting evidence regarding the retention and cariespreventive effect of glass ionomer sealants [16][17][18] , metaanalysis conducted to compare the caries-preventive effect of glass ionomer cement with resin-based fissure sealants found no evidence that either material was superior to the other in the prevention of dental caries 19,20) . Therefore, the aim of this randomized clinical trial was to compare the retention and caries-preventive effect of glass ionomer and resin-based sealants among 6-9-year-old children.…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite differences in their retention, systematic reviews have reported no evidence of caries-preventive superiority of either material. 3,4,7,8 In the past, low-and medium-viscosity glass-ionomers were used as sealant material but these have been replaced by high-viscosity glass-ionomers, as the latter have increased mechanical properties, which have enhanced sealant retention. 9 Retention of highviscosity glass-ionomers may further be increased through the development of new formulas in the glass-ionomer technology, such as has been reported regarding its powder composition.…”
Section: Introductionmentioning
confidence: 99%
“…A definição da escolha desses materiais como selantes tem motivado uma significativa variedade de estudos comparativos entre os selantes resinosos e os ionoméricos das mais diversas procedências, tendo-se em consideração as características básicas destes produtos [9][10][11] . Devemos considerar que a utilização dos cimentos ionoméricos como materiais seladores de fóssulas e fissuras deve-se ao fato de ter sua indicação para dentes em erupção e durante a maturação do esmalte.…”
Section: Introductionunclassified